Comparative analysis of two models of progressive failure of slope - He, Shuting; Lu, Lier; Yang, Liping; Lu, Yingfa (Frontiers in Earth Science, 2026)
The physical significance of traditional slice method for slope stability analysis involves reducing the peak strength of slices to characterize the degree of strength degradation in the post-failure zone of geological materials. This study applies the partial strength reduction method, using the unbalanced thrust method as an example to extend its traditional assumptions. By employing both a perfect elasto-plastic model and a novel shear stress-strain complete process constitutive model method, an extended slice method is proposed to simulate the progressive failure process of landslides, the two methods for determining the critical stress state of slices are also presented. This approach tightly links traditional landslide stability analysis with deformation behavior, revealing the stepwise movement characteristics of critical states during landsliding. Landslide failure occurs when the final slice reaches the critical state. Utilizing the Daochi Village landslide in China as a case study, the unbalanced thrust slice method under two modeling frameworks reveals evolutionary characteristics of physical-mechanical parameters during progressive failure. Results indicate that both slice models can effectively describe the progressive failure process of the Daochi Village landslide. The stability coefficient derived from the traditional partial strength reduction perfect elasto-plastic model exceeds that of the complete process constitutive model.